Rate and extent of losses from top spoilage in pilot-scale, horizontal silos - Dickerson, J.T.; Bolsen, K.K.; Brent, B.E.; Lin, C.; Boyer, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Corn and forage sorghum silages were stored in pilot-scale silos for 180 days, and dry matter (DM) and organic matter (OM) recoveries and estimated OM recovery were measured at three depths within the top 3 ft. of silage. The unsealed silages deteriorated badly in the top 12 in. Actual DM and OM losses in the top 24 in. were higher in unsealed than sealed silages at each successive storage period (7 to 180 days). The unsealed silages began to deteriorate immediately in the top 12 in. in both crops, and deterioration progressed to the second 12 in. by 90 days post-filling. Sealing immediately after filling preserved more DM and OM after 180 days in the top 12 in. than delayed sealing. Silages from both crops, when sealed immediately and treated with a mold inhibitor, Top Savor®, had the highest DM and OM recoveries in the 0- to 12-in. depth at 7 days post-filling. Organic matter recoveries estimated by an equation using silage ash content were highly correlated (r>.93) to actual OM recoveries in all unsealed silages. Estimated and actual OM recoveries were not highly correlated in sealed silages, particularly below the top 12 in., where OM losses were quite low in both crops.
Keywords: Beef; Silage; Top spoilage; Pilot-scale; Ash